ANALISIS BAKTERI FECAL STREPTOCOCCUS DI PERAIRAN PANTAI SELAT RUPAT, PROVINSI RIAU - Yoswaty, Dessy (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
The higher activity of the community in coastal waters, together with the higher the lev-el of pollution from domestic sewage and industrial waste, impacts on the quality of marine waters. Domestic waste pollution (mainly the result of human excretion), can increase the number of microorganisms. fecal Streptococci bacteria can be used as an indicator of - marine pollution. Toxin content of fecal Streptococci bacteria, if it is in the human digestive tract, can cause diarrhea, nausea and abdominal pain. The study aims to analyze the distribution of fecal Streptococci bacteria in coastal waters of the Strait of Rupat. The research was conducted from March-April 2012 in P. Mentele, P. Rampang, P. Payung, P. Baru and P. Mampu, using the survey method. Fecal Streptococci bacteria was analyzed at the Laboratory of Marine Microbi-ology Faperika, Riau University. Total test of fecal Streptococci bacteria on KF Streptococci medium and identification of isolates was determined by biochemical tests (Cappuccino & Sherman, 2001). The analysis showed that total of - fecal Streptococci bacteria 1.5 x 102 to 5.2 x 105 cells/gram sample, colonies of bacteria growing red. Total of fecal Streptococci bacteria is highest in P. Mentele, while the lowest in P. Baru. The results of water quality in the Strait of Rupat was still below those of the standard threshold. Overall, the content of Fecal Strepto-cocci bacteria is low, not categorized as polluted waters